PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK DI KELAS VIII SMP ANGKASA LANUD SUTAN SJAHRIR PADANG - Yanti, Rahmi (Departemen Matematika, 2023)
Understanding of mathematical concepts is one of the objectives of learning mathematics that must be possessed by students. However, the ability to understand mathematical concepts of class VIII students at SMP Angkasa Lanud Sutan Sjahrir Padang is still low. One of the efforts that can be made to increase students' understanding of mathematical concepts is by applying the Numbered Heads Together cooperative learning model. This study aims to analyze and compare the ability to understand mathematical concepts of students who learn using the Numbered Heads Together cooperative learning model better than those who learn using direct learning in class VIII SMP Angkasa Lanud Sutan Sjahrir Padang. This type of research is quasy experiment with the research design is Static Group Design. The population in this study were class VIII students of SMP Angkasa Lanud Sutan Sjahrir Padang who were enrolled in the 2022/2023 school year. The sample in this study was determined using the Simple Random Sampling technique with class VIII.3 as the experimental class and class VIII.2 as the control class. The data obtained in this study were analyzed using the Normality Test, Homogeneity Test, and t test. Based on the results of the analysis of mathematical concept understanding tests with a significant level of α = 0.05, P - value = 0.001 is obtained because P - value < α then rejects . This shows that students' understanding of mathematical concepts who learn using the Numbered Heads Together cooperative learning model is better than those who learn using the direct learning model in class VIII SMP Angkasa Lanud Sutan Sjahrir Padang.Keywords —Understanding of mathematical concept, Numbered Heads Together, Direct Learning.